The Inculcation of Values and Food Security in the Turun Sawah Tradition in Denai Lama Village, Pantai Labu District - Nasution, Annisa; Ritonga, Sakti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study explores the inculcation of values and food security within the Turun Sawah tradition in Denai Lama Village, Pantai Labu District. Data were collected through interviews, observations, and documentation. The findings indicate that the Turun Sawah tradition plays a crucial role in preserving local culture, maintaining food security, and enhancing the community’s economy through its agrotourism potential. As part of the agrarian heritage, this tradition not only reflects gratitude to God but also fosters values of solidarity, mutual cooperation (gotong royong), and cultural identity among younger generations. Despite significant challenges in engaging the younger generation—particularly in the face of globalization and shifting societal values—various creative approaches can be employed to ensure the sustainability of this tradition. Integrating traditional practices with modern technology, such as cultural festivals and agrotourism development, can enhance the interest of younger generations and the broader community. Furthermore, the Turun Sawah tradition significantly contributes to food security through crop diversification, supporting sustainable agriculture at the local level.